2019
DOI: 10.1016/j.jid.2019.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Age and Mothers: Potent Influences of Children’s Skin Microbiota

Abstract: The evolution of a child’s skin microbiome is associated with the development of the immune system and skin environment. As only few studies have analyzed the microbiota in young children, we investigated changes in the skin microbiota of children (158 subjects; ≤10 years old) and compared the microbiota structures between children and their mothers using 16S rRNA gene amplicon sequencing. Sample location and age were the primary factors determining a child’s skin bacterial composition, which differed signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
58
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 59 publications
14
58
2
1
Order By: Relevance
“…Previous studies also found Streptococcus 19 and Porphyromonas 19,31 among the dominant genera of the bacterial cutaneous microbiota in healthy dogs. Interestingly, a recent study of the bacterial skin microbiota of children and their mothers, noted that the genus Streptococcus was more abundant in the early-life microbiota 32 , like in our study. In earlier studies using culture-based methods, Acinetobacter was among the most common commensal bacteria isolated from the skin of healthy dogs and in was present in at least 50% of healthy dogs in a study using amplicon sequencing 26 .…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Previous studies also found Streptococcus 19 and Porphyromonas 19,31 among the dominant genera of the bacterial cutaneous microbiota in healthy dogs. Interestingly, a recent study of the bacterial skin microbiota of children and their mothers, noted that the genus Streptococcus was more abundant in the early-life microbiota 32 , like in our study. In earlier studies using culture-based methods, Acinetobacter was among the most common commensal bacteria isolated from the skin of healthy dogs and in was present in at least 50% of healthy dogs in a study using amplicon sequencing 26 .…”
Section: Discussionsupporting
confidence: 80%
“…A similar observation was made in a previous study targeting V1-V3 26 that described Cutibacterium as predominant in axilla, but not in groin samples. On the human skin, Cutibacterium is moreover positively correlated with age and thus less abundant in the early-life microbiota 32 . It would be interesting to assess the development of the canine skin in a longitudinal study to corroborate such differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Site-specific tropism has been shown down to a strain-level, indicating colonization competition occurring even at high phylogenetic resolution, which may have important implications for the development of therapeutics (Byrd et al, 2018;Conlan et al, 2012). Employing 16S ribosomal RNA amplicon sequencing, Zhu et al (2019) analyzed swabs obtained from face (cheek), central calf, and ventral forearm skin of 158 children and 50 mothers randomly selected from the cohort. Although Zhu et al (2019) found decreased facial diversity compared with other skin sites, this was only significant in 1-year-old children.…”
Section: Characterizing Skin Site-preference Colonization In the Pedimentioning
confidence: 99%
“…The cutaneous microbiome is home to a commensal population of approximately 1 Â 10 10 bacteria per 1.8 m 2 , which guards against the invasion of pathogens and breaks down natural products (Byrd et al, 2018;Zhu et al, 2019). Emerging evidence suggests that early microbial exposure may be critical to immune homeostasis and long-term health outcomes.…”
mentioning
confidence: 99%